A genealogy of the French 'Collège': the emergence of an institution of Deleuzean control - Matuszewski, Samuel John (2018)
This thesis constitutes the first analysis of the development of the French education system and the emergence of the French 'collège' in relation to Gilles Deleuze’s assertion that, in the post-war period, the disciplinary societies described by Michel Foucault have entered into crisis and that a new ‘control society’ is emerging. The first chapter of the thesis establishes the theoretical framework to be applied, elucidating the connections between Foucault’s concepts of power and 'dispositif' and Deleuze’s concepts of desire and 'agencement', before considering how historical change emerges through the intensification of strategies of power. The rest of the chapter outlines the abstract traits of discipline and then control and considers how these strategies of power might be actualised in the institution of the school. The second chapter applies this framework to the development of the education system established under the Third Republic, which is found to consist of three separate disciplinary 'dispositifs' of education that actualise distinct logics of education. The third chapter traces the intensification of strategies of power responding to the logics of the three institutions identified in the previous chapter and the transformations of the education system that this provokes before showing the emergence of the 'collège' from the confluence of these intensified logics, which establishes it as an institution of control traversed by a modulation of disciplinary logics. The 'collège' is then also shown to develop governance structures that promote modulation as the local negotiation of the institution. The thesis argues that the emergence of the 'collège' marks the beginning of a shift from discipline to control in the French education system.